If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(n + 1) + -2n = 0 Reorder the terms: 3(1 + n) + -2n = 0 (1 * 3 + n * 3) + -2n = 0 (3 + 3n) + -2n = 0 Combine like terms: 3n + -2n = 1n 3 + 1n = 0 Solving 3 + 1n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 1n = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 1n = 0 + -3 1n = 0 + -3 Combine like terms: 0 + -3 = -3 1n = -3 Divide each side by '1'. n = -3 Simplifying n = -3
| -2z+13z+13z-20z=-20 | | 0=4+2n | | 13+b=-4 | | 4/7y-8=2/7y-10 | | 2x-14y=22 | | 3(4x+5)-3y=-15 | | 8-2x=-13 | | 8(-2i)(-5-4i)= | | (8(-3)-1)-(-3)+3= | | 82(0.006889-x^2)=2x | | 3x-3y=4x+5 | | 19=4-2x | | 32x-4=3 | | -16a+11a+7a=-16 | | w/- | | 82(0.006888-x^2)=2x | | -16+y=5 | | 6-a=10-9 | | 4(x-6)=21 | | -3p+13p+14=-16 | | 2*.2-3+7+7+3*.2-10= | | (3x+3)=(4x-5) | | 15(t+2)2+9t=-90 | | 2x+5(.3-2.3)=3 | | r=0.301 | | 12+6r=-4r-5-7r | | y=10*x+500 | | -5x+4-3(x-1)=-3x-(4x-1)+3 | | 13q-12q+q-2=12 | | 1.8x=.25 | | 100=x+10x | | 3x-3(4x+5)=-15 |